238 MRCS Performance Predicts Surgical Career Outcomes. (12th October 2021) - Ellis, R; Scrimgeour, D; Cleland, J; Lee, A; Brennan, P
Abstract: Aim: Successful completion of the MRCS examination is mandatory for progression into higher surgical (registrar) training in the UK. National selection for training programmes is a highly competitive process. Despite this, the ranking of applicants does not currently include MRCS performance scores. This offers a unique opportunity to compare two independent assessments of surgical trainees to establish whether MRCS performance can predict future surgical career outcomes and competitiveness in training. Method: All UK candidates who attempted MRCS between 2007-2020 were matched to career outcome data using the GMC list of registered medical practitioners and anonymised (n = 2910). Chi-squared tests determined associations with first attempt MRCS pass/fail outcomes. Multinomial regression models were developed to establish the predictive power of success at MRCS in determining surgical specialty and training deanery choices. Results: There was statistically significant variability in MRCS Part A pass rates, ranging from 55.1%-76.7% between surgical specialties ( P =0.001) but no significant variability in Part B pass rates ( P =0.655). There was significant variability in Part A and Part B pass rates between training deaneries ( P =0.010 and P =0.036 respectively). Pass rates ranged from 59.9%-77.7% for Part A and 70.1%-85.0% for Part B between training deaneries. Those in more competitive specialties and training deaneries performed better in MRCS in terms of first attempt pass rate, scores and number of attempts taken to pass. Conclusions: MRCS performance is an early predictor of surgical career choice and competitiveness. Trainees who perform well at MRCS are more likely to enter competitive surgical specialties and training deaneries.